The Impact of Small Enterprise Activity on the Regional Development. The Case of the Podkarpackie Voivodeship - Grzęda, Łukasz; Kozak, Sylwester (Management and Administration Journal, 2019)
The goal of the study is to examine the impact of small enterprise activity on the regional economic growth on the example of counties in the Podkarpackie voivodeship. The research has shown that both, the increase in the number of already operating and the number of newly registered small enterprises positively contribute to the economic development of the county measured by the total value of sales and the per capita value sales of production manufactured in a given county, as well as the number of employees employed there. The research also indicates that the volume of production of enterprises located in a given county is positively affected by the increase in realized investment outlays as well as the upward trend in GDP of a given voivodeship. The research is based on the data from the CSO Local Data Bank for the years 2005-2016. Estimation of the models was carried out using panel regression.